Synthesis of both enantiomers of the docosahexaenoic acid ester of 13-hydroxyoctadecadienoic acid (13-DHAHLA). Issue 52 (26th December 2019) - Vik, Anders; Hansen, Trond Vidar; Kuda, Ondrej
Graphical abstract: Highlights: Syntheses of both enantiomers of 13-DHAHLA was achieved. A recent and convenient protocol for making vinylic iodides was used. Z-selective alkyne reduction was achieved by the use of activated zinc (Cu/Ag). The Corey-Fuchs and the Ohira-Bestmann reactions were used to generate alkynes. Abstract: Recently, several different classes of endogenous lipids have been reported that display antidiabetic and anti-inflammatory effects. Due to their minute presence in human samples, access to synthetic material of each enantiomer becomes necessary for exact structural elucidation and extensive biological evaluation. Herein we report the multi-milligram synthesis of both enantiomers of the docosahexaenoic acid ester of 13-hydroxyoctadecadienoic acid (13-DHAHLA) from commercially available starting materials.